Pendekatan Geomorfologi Dalam Survei Kejadian Erosi - Lihawa, Fitryane (Jurnal Pelangi Ilmu, 2009)
Geomorphology is the study of land shape, a process that causes the alteration of land shape and on both sides relationship between land shape and process of shape formation. In its application, Geomorphology is required in many fields which need land shape information and its implementation. Geomorphologic exploration results land classification into geomorphologic units. Erosion survey, by using geomorphologic approach, results some important information in land shape alteration such as to determine the cartography of design erosion, the cartography of erosion development, plain distribution into some 0erosion units that is marked by erosion intensity and the estimation of sediment result that is come from erosion process.